2009
DOI: 10.1111/j.1467-789x.2009.00570.x
|View full text |Cite|
|
Sign up to set email alerts
|

Efficacy of behavioural interventions in managing atypical antipsychotic weight gain

Abstract: Atypical antipsychotic treatment is associated with weight gain and increased metabolic risk. This systematic literature review evaluates the current research on the effectiveness of behavioural interventions in treating and preventing atypical antipsychotic weight gain and reducing metabolic risk, describes characteristics of interventions implemented and discusses findings in the context of the RE-AIM framework. Sixteen studies were identified. When initiated at the start of treatment with an atypical antips… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
42
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(44 citation statements)
references
References 31 publications
1
42
1
Order By: Relevance
“…Three of the seven randomized controlled trials did not find statistically significant weight loss outcomes. Two were weight loss programs (10,27), and one was a fitness intervention (36). The other four randomized controlled trials—all weight loss programs—reported that their program participants achieved statistically significant weight loss when they were compared with their respective control groups.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Three of the seven randomized controlled trials did not find statistically significant weight loss outcomes. Two were weight loss programs (10,27), and one was a fitness intervention (36). The other four randomized controlled trials—all weight loss programs—reported that their program participants achieved statistically significant weight loss when they were compared with their respective control groups.…”
Section: Resultsmentioning
confidence: 99%
“…This article seeks to address this question by systematically reviewing studies that report the health outcomes of lifestyle interventions evaluated in this population. Past reviews of the literature have focused mainly on weight management treatments among individuals with schizophrenia (8,9) or on the efficacy of behavioral interventions in managing weight gain associated with the use of second-generation antipsychotic medications (10). The review presented here builds on this previous work and provides a comprehensive literature review of interventions that not only focuses on weight but also examines exercise, health promotion, and self-management activities; expands the patient population to include other diagnostic categories (for example, bipolar disorder and schizoaffective disorder) represented in the population with serious mental illness (11); and assesses the inclusion of persons from racial and ethnic minority groups in these studies.…”
mentioning
confidence: 99%
“…Lifestyle changes are considered the first line of treatment to decrease cardiovascular risks in people with metabolic syndrome, 30 being more effective than pharmacological interventions. 3,8,15,20,[31][32][33][34][35][36][37][38][39][40] Forensic psychiatrists try to treat obesity on a case-by-case basis by imposing limits on junk food, 41 but systematic control over diet and behavioural contingencies is quite feasible in psychiatric hospitals. 33 A simple measure already taken in the study hospital is to reduce the regular diet to no more than 2400 kcal/day, and therapy for forensic inpatients with metabolic syndrome that supports dietary and activity changes is proposed.…”
Section: Discussionmentioning
confidence: 99%
“…In a meta-analysis on randomised, controlled, cognitive-behavioural weight loss trials, Bonfioli et al (2012) concluded that in patients with psychosis, a weight loss of 0.98 points in BMI (corresponding to a loss of 3.12% of initial weight) was demonstrated from pooled data. Weight loss programs can also prevent weight gain associated with antipsychotic use and even promote weight loss (Chen et al, 2009, Gabriele et al, 2009, Menza et al, 2004, Vreeland et al, 2003. In a study by Zhang et al (2012), patients with psychotic spectrum disorders experienced a greater percent baseline weight loss at 12 months, and greater percent BMI loss at 9 and 12 months than people suffering from other psychiatric disorders and no psychiatric disorder.…”
Section: Accepted M Manuscriptmentioning
confidence: 99%